White Paper: Advancing Sustainability in Aquatic Food Systems Through the AquaIndex - Ramachandran, Rohit; Saito, Osamu; Rossignoli, Cristiano; Dam Lam, Rodolfo; Yagi, Nobuyuki; Ito, Shin-ichi; Kondoh, Michio (WorldFish, 2024)
This white paper outlines the AquaIndex’s conceptual framework, highlights key outcomes from the kick-off workshop, and provides a roadmap for its development and implementation. The paper also issues a call to action, urging stakeholders to collaborate in this ambitious effort to achieve sustainable, equitable, and resilient aquatic food systems.